ఆంధ్ర సారస్వత పరిషత్తు స్వర్ణోత్సవ సంచిక - (:unkn) unknown (Andhra Saraswata Parishath, 1994)
It;s about history of Andhra Saraswata Parishathu. It's a special edition on the occassion of its silver jubliee.
Andhra Saraswata Parishathu Swrnothsava Sanchika
Keywords: Telugu; Literature; Telugu; Telugu